2016
DOI: 10.1111/dme.13175
|View full text |Cite
|
Sign up to set email alerts
|

Variants associated with autoimmune Type 1 diabetes in Japanese children: implications for age‐specific effects of cis‐regulatory haplotypes at 17q12‐q21

Abstract: The results indicate that rs2290400 in GSDMB and polymorphisms in INS and CTLA4 are associated with the risk of Type 1 diabetes in Japanese children. Importantly, cis-regulatory haplotypes at 17q12-q21 encompassing rs2290400 probably determine the risk of autoimmune Type 1 diabetes predominantly in early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…A recent study performed by the present author group indicated a significant role for SNPs in INS and CTLA4 genes in the development of Type 1 diabetes in Japanese children . The results of this recent study together with those of the present study indicate that, immune functional variants of the HLA , INS , CTLA4 and FUT2 genes, are contributory risk factors for Type 1 diabetes in an ethnicity‐independent manner.…”
Section: Discussionsupporting
confidence: 78%
“…A recent study performed by the present author group indicated a significant role for SNPs in INS and CTLA4 genes in the development of Type 1 diabetes in Japanese children . The results of this recent study together with those of the present study indicate that, immune functional variants of the HLA , INS , CTLA4 and FUT2 genes, are contributory risk factors for Type 1 diabetes in an ethnicity‐independent manner.…”
Section: Discussionsupporting
confidence: 78%
“…In a previous study, we reported a significantly higher odds ratio of IDDM2 in Japanese patients with type 1 diabetes than in Caucasian patients with type 1 diabetes . Ayabe et al . recently reported a high odds ratio for IDDM2 using SNP rs689 in Japanese patients with type 1 diabetes, which prompted us to again compare the odds ratio for the rs689 genotype between Japanese and Caucasian patients with type 1 diabetes, and the results are shown in Table .…”
Section: Discussionmentioning
confidence: 79%
“…The SNPs, rs3757247 and rs11755527, which are in tight linkage disequilibrium (LD), have been reported to be associated with type 1 diabetes in Caucasian individuals. Ayabe et al . confirmed the association of rs3757247 in Japanese individuals with childhood‐onset type 1 diabetes.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations